Efektivitas Pemasangan Alat Point Of Sales Terhadap Kepatuhan Wajib Pajak Restoran Di Kabupaten Buleleng - kadek wiraksini; Ni Luh Gede Erni Sulindawati (Universitas Pendidikan Ganesha, 2025)
This research was carried out at the Buleleng Regency BPKPD office. The aim of this research is to determine the effectiveness of installing point of sales equipment on restaurant tax compliance in Buleleng Regency. The method in this research is descriptive qualitative, namely providing exposure related to the effectiveness of installing point of sales equipment on restaurant tax compliance in Buleleng Regency. Furthermore, this research uses the source triangulation method to test the credibility of data by checking data that has been obtained from various data sources such as interviews, archives, observations and other documents. Based on the research results, it is known that the installation of Point of Sales equipment has proven effective in increasing restaurant tax compliance in Buleleng Regency. Installing point of sales tools in restaurants helps record transactions in real time, reduces human errors in tax calculations and reporting, and facilitates electronic tax payments